Pick and place robot gripper for relay assembly line / Ahmed Jaffar and Noriah Yusoff (Faculty of Mechanical Engineering and University Publication Centre (UPENA), 2008)
The most important basic task in any robotic assembly line where industry tend to ignore is the pick and place operation. Generally, the pick and place operation consists of guiding the robot s arm or manipulators to the targets position, picking up or releasing objects and moving the objects to new target locations using a specially designed or off the shelve grippers. Grippers are end-effectors used to grasp and hold objects for a particular assigned task. Despite the fact that robotic grippers' studies are a mature subject, yet it is still a rewarding area for research development, especially to the manufacturing industry. This paper describes the development of a new gripper for the pick and place of a relay assembly line in an electronics manufacturing company. The research findings are based on case study conducted at the local electronic company. The present assembly operation in one of the station of the identified electronic parts is still done manually. CAD/CAM software was exploited extensively to model a geometrical design of the robot gripper. The gripper s performance was examined by studying the gripper force and control analysis. With the analytical study of the gripper parameters required to meet the design specifications of the product, a prototype of the robot gripper was fabricated. Financial and production analysis in terms of cost comparison before and after the implementation of the new pick and place set-up was also carried out to examine the viability of the project. The final results shown that it can have a significantly increased in productivity, revenue and profit to the company if it is to be implemented at the plant. Implementation of this will also creates flexibility in the assembly line setup for further development to a fully automated relay production line.